2017
DOI: 10.17957/ijab/15.0384
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Resistance to Rice Blast and False Smut of 18 Varieties of Hybrid Rice in Sichuan Province, China

Abstract: Rice blast and false smut are severe diseases of rice reducing not only rice yield but also affect grain quality. The most effective and economical mean of controlling diseases is to breed disease-resistant rice cultivars. Here, we used 18 hybrid rice varieties for identifying their functional rice blast resistance genes, and for estimating their sensitivities to false smut disease. This experiment was conducted in Sichuan Province, China in 2012-2014. The results showed that the Pi2 and Pik loci have strong r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Planting‐resistant rice varieties are undoubtedly an economically viable and effective measure to deal with the threat of rice false smut to the stability of RC systems. In field experiments, Li et al identified 6 resistant rice varieties by measuring significant differences in the diseased panicle rate and disease index among 18 rice varieties (Li et al, 2017). We investigated the false smut resistance of 9 rice varieties in 2019 and 9 rice varieties in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Planting‐resistant rice varieties are undoubtedly an economically viable and effective measure to deal with the threat of rice false smut to the stability of RC systems. In field experiments, Li et al identified 6 resistant rice varieties by measuring significant differences in the diseased panicle rate and disease index among 18 rice varieties (Li et al, 2017). We investigated the false smut resistance of 9 rice varieties in 2019 and 9 rice varieties in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of rice false smut in our experiments varied significantly based on the year of the experiment (Tables 2 and 3), and meteorological factors are likely to be major reasons for this difference. It has been reported that late sowing (transplantation) increased the severity of false smut (Atia, 2004; Li et al, 2017). This effect might be attributed to early transplantation leading to early maturation of rice plants and escape from pathogen infection, because the RH and temperature associated with late sowing provide better conditions for rice false smut infection and the appearance of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yangtze and Huaihe river basins are the central regions for planting japonica rice and an area with a high incidence of rice blast (Zhang et al, 2022). However, most localized and cloned rice blast genes are primarily derived from indica rice varieties and there is a significant difference in the distribution of recessive and dominant resistant genes between indica and japonica (M. Li, 2021;Shen et al, 2021;Wu et al, 2021;Yan et al, 2022;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Li Mingyou (2021) investigated 14 genetic markers of R genes for 218 japonica rice varieties/lines that have recently been widely cultivated in the Jiangsu region. He reported that Pib had the highest distribution frequency in the population, reaching 79.82%, and Pigm had the lowest frequency.…”
Section: Introductionmentioning
confidence: 99%